2019
DOI: 10.1177/2050312119850400
|View full text |Cite
|
Sign up to set email alerts
|

‘Menstrual blood is bad and should be cleaned’: A qualitative case study on traditional menstrual practices and contextual factors in the rural communities of far-western Nepal

Abstract: Objective: Unhealthy menstrual practices and the contexts surrounding them should be explored and clearly understood; this information could be useful while developing and implementing interventions to increase hygienic practices during menstruation and consequently increase health and well-being of women. Therefore, this study was conducted to explore traditional menstrual practices and the contextual factors surrounding the practices in the rural communities of far-western Nepal. Methods: This was a qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 24 publications
5
49
2
1
Order By: Relevance
“…Despite several interventions to address menstrual taboo (e.g., awareness raising, community sensitization, and legislation), the majority of young girls and women are still forced to follow different traditional menstrual practices (e.g., chhaupadi, untouchability and restrictions) [ 15 ]. Anecdotal reports from the field [ 7 , 11 , 14 ] and empirical studies [ 9 , 10 ] have suggested that these interventions have only been effective for a short duration of time for several reasons. For instance, a baseline programme evaluation report published in 2015 suggested that community stakeholders were reluctant to participate in interventions aimed at abolishing such practices, although most of them initially showed their interest and support [ 7 ].…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite several interventions to address menstrual taboo (e.g., awareness raising, community sensitization, and legislation), the majority of young girls and women are still forced to follow different traditional menstrual practices (e.g., chhaupadi, untouchability and restrictions) [ 15 ]. Anecdotal reports from the field [ 7 , 11 , 14 ] and empirical studies [ 9 , 10 ] have suggested that these interventions have only been effective for a short duration of time for several reasons. For instance, a baseline programme evaluation report published in 2015 suggested that community stakeholders were reluctant to participate in interventions aimed at abolishing such practices, although most of them initially showed their interest and support [ 7 ].…”
Section: Main Textmentioning
confidence: 99%
“…We did not follow a systematic process but based the review on general topic-related keyword search (e.g., "chhaupadi", "menstrual health interventions", "menstruation management intervention", "menstruation management programme", "menstrual restrictions", "menstrual stigma", "menstrual taboo") on PubMed, Google Scholar and official websites of non-governmental organizations implementing programmes and interventions to address menstrual taboo in Nepal. Altogether seven programme or news reports [5][6][7][11][12][13][14] and six peerreviewed papers [1,2,9,10,15,16] explaining menstrual taboo and/or menstrual management interventions were included in the review. We also looked for additional relevant programme reports and peer-reviewed papers [4,8,[17][18][19][20][21][22] to consider implementation perspectives on how the effectiveness of the interventions can be enhanced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the Nepal government's initiative of banning the practice of Chhaupadi in 2005, followed by the "Chhaupadi Pratha" Elimination Directive in 2008, the practice still exists in some areas and communities in Nepal [15,16]. Even though this extreme practice has never been prevalent among urban Nepalese women, some socio-cultural restrictions during menstruation still exist in other societies across Nepal, specifically among different castes [17][18][19]. Some of the common socio-cultural beliefs in various castes in Nepal related to menstruation include: not touching a male member of the family, plant, tree or fruit during menstruation, not consuming pickles or dairy products, eating alone during menstruation, not entering the kitchen or places of worship, not visiting relatives, or not attending social or religious gatherings [12,20]..…”
Section: Introductionmentioning
confidence: 99%
“…El 88.0% dijo haber usado alguna vez toallas sanitarias, mientras que establecer confianza con la CM tardó aproximadamente 6 meses. Con todo, el costo inicial y la disponibilidad del dispositivo en estas zonas son barreras a considerar, en especial en las áreas que registran mayor problemática 15 .…”
Section: IIunclassified